The empowering potential of intergroup leadership: How intergroup leadership predicts psychological empowerment through intergroup relational identification and resources. Issue 12 (29th August 2020) - van der Stoep, Joost; Sleebos, Ed; van Knippenberg, Daan; van de Bunt, Gerhard
Abstract: As work increasingly transcends organizational boundaries, employee psychological empowerment benefits from resources provided by others outside of the employee's own team, department, or organization. These intergroup collaborations, however, may be inhibited by social identity and social categorization processes, so that the empowerment potential of these relations remains largely untapped. In this study ( N = 213), we demonstrate that intergroup leadership is linked to employee psychological empowerment via intergroup relational identification and access to resources. In this way, this study demonstrates the empowering potential of intergroup leadership and intergroup relational identification for employees who collaborate across group barriers. We finish this paper by discussing the main implications for both empowerment and intergroup leadership theory, suggesting fruitful avenues for future research and highlighting the practical value for those who are motivated to increase psychological empowerment among boundary‐spanning employees.